Progressive attenuation of visual global precedence across healthy aging and Alzheimer’s disease - Álvarez-San Millán, Andrea; Iglesias, Jaime; Gutkin, Anahí; Olivares, Ela I. (Frontiers in Aging Neuroscience, 2022)
In the perception of Navon hierarchical stimuli (e.g. large letters made up of small letters), young adults identify large letters faster than small ones (known as ‘global advantage’) and identify more slowly small letters when they form a different (or incongruent) large letter (known as ‘unidirectional global interference’). Since some global/local perceptual alterations might be occurring with ageing, we investigated whether these effects vary across healthy ageing and Alzheimer's disease (AD). Here, the Navon letter task was administered to 26 healthy elderly (HE), 21 adults with Mild Cognitive Impairment (MCI) and 26 AD adults. The same task was administered one year later, and different neuropsychological variables were incorporated into the analyses. The cross-sectional study revealed no global advantage but did reveal both global and local interferences in all groups when response times were analysed. Regarding discrimination sensitivity (d’), HE showed unidirectional global interference, while AD displayed better discrimination of local than global letters in the incongruent condition, which denotes less interference by global distractors than by local ones. The longitudinal study revealed that, one year later, MCI participants showed a slowdown in inhibiting local distractors in the global task, revealing a certain bias towards focus their attention on small stimuli. AD elders reflected a generalised slowing of their responses with a clear bias towards local analysis of stimuli, also suggested by their better discrimination in the incongruent local task at the second moment of assessment. Furthermore, all response timing measures in the Navon task were correlated with several neuropsychological indexes of highly sensitive neuropsychological tests, suggesting that performance in this task may also have a potential diagnostic value for differentiating typical from atypical cognitive aging. All these results support the need for a multidomain approach to define neuropsychological markers of progression towards AD, including visual perceptual organization evaluated via measures of performance quality.